Johann Christoph Gottscheds Briefwechsel - Historisch-kritische Ausgabe Band 7: August 1740 - Oktober 1741 - Gottsched, Johann Christoph (Briefwechsel, 2013)
The focus of this volume is on the world of theater. The reign of Frederick II is a subject of considerable attention in the correspondence: from Königsberg come reports about the politics of religion, and from Berlin reports about the politics of science. The Weißenfelser Society of Alethophiles was becoming successful.